2021
DOI: 10.3390/molecules26020484
|View full text |Cite
|
Sign up to set email alerts
|

Improved Safety and Anti-Glioblastoma Efficacy of CAT3-Encapsulated SMEDDS through Metabolism Modification

Abstract: 13a-(S)-3-pivaloyloxyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (CAT3) is a novel oral anti-glioma pro-drug with a potent anti-tumor effect against temozolomide-resistant glioma. 13a(S)-3-hydroxyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (PF403) is the active in vivo lipase degradation metabolite of CAT3. Both CAT3 and PF403 can penetrate the blood–brain barrier to cause an anti-glioma effect. However, PF403, which is produced in the gastrointestinal tract and plasma, causes significant gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The morphological evaluation of PTX–LNPs was carried out by transmission electron microscopy (TEM, Hitachi H-7650, Tokyo, Japan) [ 8 ]. Two drops of the PTX–LNPs were deposited on a film-coated copper grid and negatively stained with 1% ( w / v ) phosphotungstic acid for 5 min before observation under an electron microscope [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The morphological evaluation of PTX–LNPs was carried out by transmission electron microscopy (TEM, Hitachi H-7650, Tokyo, Japan) [ 8 ]. Two drops of the PTX–LNPs were deposited on a film-coated copper grid and negatively stained with 1% ( w / v ) phosphotungstic acid for 5 min before observation under an electron microscope [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…A small number of SEDDS-based products have already been successfully introduced into the pharmaceutical market, with none of them loading drugs for the treatment of neurological disorders. Until now, several in vivo assays using oral SEDDS have been carried out for neuropharmaceuticals brain targeting [ 4 , 6 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 70 ], but only a few in vivo pre-clinical studies have been reported for IN administration of neurotherapeutics loaded in SEDDS. In fact, only six studies were found that investigated the IN administration of neurotherapeutics loaded in SEDDS: clonazepam [ 45 ], diazepam [ 44 ], and perampanel [ 28 ] for epilepsy treatment; Bdph for glioblastoma treatment [ 4 ]; huperzine A [ 30 ] for Alzheimer’s disease; and naringin [ 5 ] as a neuroprotective for Alzheimer’s and Parkinson’s disease.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
“…This demonstrates the advantages of using nasal SEDDS rather than a simple nasal solution, the oral route or the invasive IV route for brain delivery of drugs. By analyzing Table 2 , it is noted that, despite the pharmacokinetic evaluation, some authors also performed behavioral studies to compare the efficacy and safety of drugs loaded in SEDDS administered with those of simple solutions, suspensions or commercial preparations of the same drugs [ 4 , 25 , 29 , 31 , 32 , 33 , 46 , 48 , 49 , 50 ]. For the case of glioblastoma treatment, efficacy was directly assessed after oral administration of chlorogenic acid SMEDDS [ 48 ] or the new prodrug 13a-(S)-3-pivaloylocyl-6,7-dimethoxyphenanthro(9,10-b)-indolizidine (CAT3) [ 49 ].…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
See 2 more Smart Citations